Anti-aging organic zirconium phosphate / polymer modified asphalt and preparation method thereof
By using zirconium organophosphate to react with polymer in polymer-modified asphalt to form a new crosslinking network, the problem of easy aging of polymer-modified asphalt is solved, which significantly improves storage stability and anti-aging properties, and extends the road surface life.
Patent Information
- Application Number
- CN202510077916.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Polymer modified asphalt is prone to aging during use, resulting in degradation of performance and problems such as loose road surfaces, peeling, and cracks, which affects the performance and driving safety, and at the same time poor storage stability.
Using zirconium organophosphate as a crosslinking agent, reacts with polymer modifiers to form a new zirconium phosphate-polymer crosslinking network, increases the density of the crosslinking network, avoids the agglomeration of inorganic particles, and improves physical rheology performance through sulfur participation in the crosslinking reaction.
It significantly improves the storage stability and anti-aging properties of polymer modified asphalt, extends the life of asphalt pavement, and improves physical rheology performance.
Smart Images

Figure BDA0005247654900000111 
Figure BDA0005247654900000112 
Figure BDA0005247654900000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building material preparation, and in particular to an aging-resistant organic zirconium phosphate / polymer modified asphalt and a preparation method thereof. Background Art
[0002] Polymer modified asphalt is increasingly widely used in road engineering due to its excellent performance. However, polymer modified asphalt pavement is prone to aging during service, resulting in a decline in its performance. Aged materials can cause road problems such as looseness, peeling, cracks, potholes, etc., which seriously affect the performance and driving safety of polymer modified asphalt pavement, which significantly increases the maintenance cost of the pavement and also reduces the service life of the pavement. In addition, the low density of the polymer causes segregation in traditional polymer modified asphalt, which seriously affects the storage stability of polymer modified asphalt. Therefore, the development of aging-resistant polymer modified asphalt materials with good storage stability is of extremely important engineering significance for the construction of high-quality and long-life pavements.
[0003] Adding anti-aging agents is an important way to improve the anti-aging performance of asphalt. Adding UV531, alkaline lignin, carbon black, inorganic nanomaterials, layered double hydroxides, etc. to polymer modified asphalt can improve the anti-aging ability of polymer modified asphalt. In order to improve the modification effect of inorganic nanomaterials and layered double hydroxides, they are also surface-modified. In recent years, the research on inorganic nanomaterials, layered double hydroxides, or their surface-modified products as asphalt anti-aging agents has received more and more attention. However, most of the existing technologies are to simply physically blend inorganic nanomaterials, layered double hydroxides, or their surface-modified products with polymer modifiers and asphalt. The modified asphalt prepared in this way still has some problems, such as polymer modifiers will separate from asphalt due to their low density, and surface modification cannot completely solve the agglomeration phenomenon of inorganic nanomaterials and layered double hydroxides, which will lead to poor storage stability of modified asphalt. The agglomeration phenomenon of inorganic nanomaterials and layered double hydroxides will affect the improvement of asphalt anti-aging performance.
[0004] The present invention combines the current status of research on polymer modified asphalt and proposes a new idea for preparing aging-resistant polymer modified asphalt with good storage stability. Summary of the invention
[0005] The purpose of the present invention is to provide an aging-resistant organic zirconium phosphate / polymer modified asphalt and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention: an aging-resistant organic zirconium phosphate / polymer modified asphalt, the raw materials of which include, by weight: 2 to 6 parts of organic zirconium phosphate, 3 to 10 parts of polymer modifier, 100 parts of base asphalt, 1 to 3 parts of solubilizer, and 0.02 to 0.05 parts of sulfur.
[0008] Compared with traditional polymer modified asphalt, the aging-resistant organic zirconium phosphate / polymer modified asphalt of the present invention adopts organic zirconium phosphate as a cross-linking agent to participate in the formation of the polymer cross-linking network, and obtains a new cross-linking network of zirconium phosphate-polymer. The addition of organic zirconium phosphate increases the density of the polymer cross-linking network, and alleviates the segregation problem of modified asphalt caused by the low density of traditional polymers. At the same time, this new network structure makes the zirconium phosphate evenly dispersed in the asphalt, avoiding the agglomeration of inorganic particles. In addition, the zirconium phosphate with a layered structure is evenly dispersed in the modified asphalt, which can reduce the oxidation of organic molecules in the asphalt, thereby improving the anti-aging performance of the asphalt, which is conducive to extending the life of the asphalt pavement. Moreover, sulfur can be used as a cross-linking agent to participate in the cross-linking reaction of organic zirconium phosphate and polymer, improve the cross-linking density of the polymer cross-linking network, thereby further improving the physical rheological properties of the asphalt.
[0009] Furthermore, the organic zirconium phosphate is obtained by surface-modifying zirconium phosphate with an organic surface modifier; the organic surface modifier is one of ethyl isocyanate acrylate, isocyanoethyl methacrylate, vinyltrimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyldiethoxysilyloxy)piperidine (PMVP).
[0010] The organic zirconium phosphate obtained by surface modification (surface grafting modification) of zirconium phosphate with an organic surface modifier carries reaction sites (the organic surface modifier grafted on the surface of zirconium phosphate provides the reaction sites), which can react with polymer modifiers to form a new cross-linked network structure, thereby improving the performance of asphalt. The layered structure of zirconium phosphate itself can also effectively prevent the oxidation of asphalt molecules.
[0011] The isocyanate in isocyanate ethyl acrylate and isocyanoethyl methacrylate can react with the hydroxyl group on the surface of zirconium phosphate to achieve surface modification. Vinyl trimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyl diethoxysilyloxy) piperidine (PMVP) rely on the reaction of silyl groups with hydroxyl groups after hydrolysis. The double bonds contained in the structures of the four organic surface modifiers can achieve cross-linking with the polymer structure.
[0012] Furthermore, the organic surface modifier is one of ethyl isocyanate acrylate and isocyanoethyl methacrylate, and the preparation steps of the organic zirconium phosphate include: mixing zirconium phosphate (ZrP) and toluene to obtain a zirconium phosphate-toluene mixture; adding an organic surface modifier and a catalyst to the zirconium phosphate-toluene mixture, and refluxing at a temperature of 80 to 120° C. for 4 to 8 hours to obtain the organic zirconium phosphate;
[0013] Alternatively, the organic surface modifier is one of vinyltrimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyldiethoxysilyloxy)piperidine, and the preparation steps of the organic zirconium phosphate include: hydroxyl-modifying zirconium phosphate to obtain hydroxylated zirconium phosphate; dispersing the hydroxylated zirconium phosphate in water, then adding a methanol solution of the organic surface modifier, stirring the reaction for 2 to 4 hours, and obtaining the organic zirconium phosphate.
[0014] When the organic surface modifier is one of ethyl isocyanate acrylate and isocyanoethyl methacrylate, toluene is selected as the reaction solvent during the surface modification process. The reason is that toluene is an inert solvent relative to isocyanate. Common solvents such as water and alcohols can react with isocyanate and affect the grafting of zirconium phosphate surface. When the organic surface modifier is one of vinyl trimethoxy silane and 1,2,2,6,6-pentamethyl-4-(vinyl diethoxysilyl) piperidine, water is selected as the reaction solvent during the surface modification process because the siloxy group can only be grafted to the zirconium phosphate surface after hydrolysis.
[0015] Furthermore, the catalyst is dibutyltin dilaurate, stannous octoate or lead octoate.
[0016] Further, the mass ratio of the zirconium phosphate, toluene, organic surface modifier and catalyst is 3:270-330:1.5-2.5:0.01;
[0017] Alternatively, the mass ratio of the hydroxylated zirconium phosphate, water and the methanol solution of the organic surface modifier is 1:8-12:8-12, and the concentration of the methanol solution of the organic surface modifier is 30-50wt%.
[0018] Furthermore, after the reflux is completed, the steps of filtering, washing with toluene and vacuum drying are also included.
[0019] Furthermore, the rotation speed of the stirring reaction is 1000-2000 rpm; after the stirring reaction is completed, the steps of filtering, washing and drying are also included.
[0020] Furthermore, the mixing of zirconium phosphate and toluene to obtain a zirconium phosphate-toluene mixture comprises: mixing zirconium phosphate and toluene, ultrasonically treating for 15 to 30 minutes, and then refluxing at a temperature of 80 to 120° C. for 20 to 40 minutes to obtain a zirconium phosphate-toluene mixture.
[0021] Furthermore, the hydroxyl-modification of zirconium phosphate to obtain hydroxylated zirconium phosphate includes: mixing zirconium phosphate and water, adjusting the pH of the mixed solution to 9 to 11, and stirring for 8 to 10 hours to obtain the hydroxylated zirconium phosphate.
[0022] Hydroxyl modification of zirconium phosphate can make the hydroxyl activity on the surface of zirconium phosphate higher and improve the surface modification efficiency.
[0023] When isocyanate ethyl acrylate or isocyanate ethyl methacrylate is used as the surface modifier, since the isocyanate group and the hydroxyl group have strong reaction activity, a good modification efficiency can be achieved without performing hydroxyl modification on the zirconium phosphate.
[0024] Furthermore, the mass ratio of the zirconium phosphate to water is 1:8-12.
[0025] Furthermore, after the stirring is completed, the steps of suction filtration and washing until the filtrate is neutral and drying are also included.
[0026] Furthermore, the polymer modifier is a polymer containing double bonds in its structure.
[0027] Further preferably, the polymer modifier includes one or more of SBS (polystyrene-butadiene-styrene triblock copolymer), SBR (polystyrene butadiene copolymer) and rubber powder (all of which are polymers containing double bonds in their structures).
[0028] SBS, SBR and rubber powder have a good modification effect on asphalt. The polymer and organic zirconium phosphate have double bonds in their structures, and the two cross-link to form a denser cross-linking network, which is conducive to alleviating the segregation of polymer-modified asphalt and improving the storage stability of polymer-modified asphalt.
[0029] Furthermore, the solubilizer is a degradation product of waste plastics; the preparation steps of the degradation product of waste plastics include: mixing waste plastics, triethylenetetramine and zinc acetate, condensing and refluxing at a temperature of 160 to 200° C. for 2 to 3 hours to obtain the degradation product of waste plastics.
[0030] The addition of waste plastic degradation products can enhance the compatibility of the new network structure with asphalt, and further enhance the storage stability of modified asphalt.
[0031] Furthermore, the condensation reflux is carried out under nitrogen protection.
[0032] Furthermore, the mass ratio of the waste plastic, triethylenetetramine and zinc acetate is 1:5 to 9:0.01.
[0033] Furthermore, the waste plastics are waste PET plastics.
[0034] Furthermore, after the condensation and reflux are completed, the steps of filtering, washing and drying are also included.
[0035] The second technical solution of the present invention: The preparation method of the above-mentioned aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following steps:
[0036] After preheating the base asphalt to 160-180°C, a polymer modifier and a solubilizer are added, and high-speed shearing is performed at a temperature of 175-195°C for 50-70 minutes; then, organic zirconium phosphate and sulfur are added, and high-speed shearing is performed at a temperature of 175-195°C for 40-60 minutes; then, the temperature is lowered to 165-185°C, and low-speed stirring is performed for 40-60 minutes to obtain the aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0037] Furthermore, the rotation speed of the high-speed stirring is 4000-5000 rpm; the rotation speed of the low-speed stirring is 1000-2000 rpm.
[0038] The present invention discloses the following technical effects:
[0039] (1) The present invention utilizes organic zirconium phosphate to react with a polymer to form a new cross-linked network structure. Compared with the traditional polymer cross-linked network, the new cross-linked network has a higher density, which is conducive to alleviating the segregation phenomenon of polymer modified asphalt. At the same time, the zirconium phosphate is evenly distributed in the network structure, avoiding the agglomeration of inorganic particles. Therefore, the aging-resistant organic zirconium phosphate / polymer modified asphalt prepared by the present invention has excellent storage stability.
[0040] (2) Zirconium phosphate is evenly distributed in the new cross-linked network, and its layered structure can produce a certain barrier effect against ultraviolet radiation and oxygen, thereby reducing the oxidation of organic molecules in asphalt, thereby improving the ability of polymer-modified asphalt to resist ultraviolet aging, which is beneficial to extending the life of asphalt pavement.
[0041] (3) The present invention uses waste plastic degradation products as solubilizers to participate in asphalt modification. During the decomposition of waste plastics, the ratio of waste plastics to decomposers can be changed according to demand, the molecular weight of the waste plastic decomposition products can be adjusted, and the solubilization effect can be regulated. Using waste plastic decomposition products as solubilizers is in line with the concept of sustainable development and provides a new idea for the treatment of waste plastics. DETAILED DESCRIPTION
[0042] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0043] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] As the first aspect of the present invention, the present invention provides an aging-resistant organic zirconium phosphate / polymer modified asphalt. The raw materials include, by weight: 2 to 6 parts of organic zirconium phosphate, 3 to 10 parts of polymer modifier, 100 parts of base asphalt, 1 to 3 parts of solubilizer, and 0.02 to 0.05 parts of sulfur.
[0048] As an embodiment of the present invention, the organic zirconium phosphate is obtained by surface-modifying zirconium phosphate with an organic surface modifier; the organic surface modifier is one of ethyl isocyanate acrylate, isocyanoethyl methacrylate, vinyltrimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyldiethoxysilyloxy)piperidine (PMVP).
[0049] As an embodiment of the present invention, the organic surface modifier is one of ethyl isocyanate acrylate and isocyanoethyl methacrylate, and the preparation steps of the organic zirconium phosphate include: mixing zirconium phosphate and toluene, ultrasonically treating for 15 to 30 minutes, and then refluxing at a temperature of 80 to 120° C. for 20 to 40 minutes to obtain a zirconium phosphate-toluene mixture; adding an organic surface modifier and a catalyst to the zirconium phosphate-toluene mixture, and refluxing at a temperature of 80 to 120° C. for 4 to 8 hours to obtain the organic zirconium phosphate;
[0050] Alternatively, the organic surface modifier is one of vinyltrimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyldiethoxysilyloxy)piperidine, and the preparation steps of the organic zirconium phosphate include: hydroxyl-modifying zirconium phosphate to obtain hydroxylated zirconium phosphate; dispersing the hydroxylated zirconium phosphate in water, then adding a methanol solution of the organic surface modifier, stirring the reaction for 2 to 4 hours, and obtaining the organic zirconium phosphate.
[0051] As a preferred embodiment of the present invention, the organic surface modifier is one of isocyanate ethyl acrylate and isocyanoethyl methacrylate, and the organic zirconium phosphate is more specifically prepared by the steps of: adding 3 parts of zirconium phosphate (ZrP) to 270-330 parts of toluene, ultrasonicating for 15-30 minutes, and refluxing at 80-120°C for 20-40 minutes to obtain a zirconium phosphate-toluene mixture; adding 1.5-2.5 parts of isocyanate ethyl acrylate or isocyanoethyl methacrylate to the zirconium phosphate-toluene mixture, and dropping 0.01 parts of a catalyst (dibutyltin dilaurate, stannous octoate or lead octoate, preferably dibutyltin dilaurate), refluxing at 80-120°C for 4-8 hours, filtering, washing with toluene, and vacuum drying to obtain the organic zirconium phosphate;
[0052] Or, the organic surface modifier is one of vinyltrimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyldiethoxysilyloxy)piperidine, and the organic zirconium phosphate has a more specific preparation step comprising: placing 10 parts of zirconium phosphate in a beaker, adding 80 to 120 parts of water, and then dropwise adding an aqueous sodium hydroxide solution (there is no requirement for the concentration of the aqueous sodium hydroxide solution) until the solution pH reaches 9 to 11, stirring at room temperature (rotation speed is 1000 to 2000 rpm) for 8 to 10 hours, then filtering and washing until the filtrate is neutral, and drying to obtain hydroxylated zirconium phosphate; dispersing 10 parts of hydroxylated zirconium phosphate in 80 to 120 parts of water, and then dropwise adding 80 to 120 parts of a methanol solution of vinyltrimethoxysilane or PMVP (concentration is 30 to 50 wt%), stirring (rotation speed is 1000 to 2000 rpm) for 2 to 4 hours, filtering, washing, and drying to obtain the organic zirconium phosphate.
[0053] As an embodiment of the present invention, the polymer modifier is a polymer containing double bonds in its structure.
[0054] As a preferred embodiment of the present invention, the polymer modifier includes one or more of SBS, SBR and rubber powder.
[0055] As an embodiment of the present invention, the solubilizer is a degradation product of waste plastics; the preparation steps of the degradation product of waste plastics include: mixing waste plastics, triethylenetetramine and zinc acetate, condensing and refluxing at a temperature of 160 to 200° C. for 2 to 3 hours to obtain the degradation product of waste plastics.
[0056] As a preferred embodiment of the present invention, after the condensation and reflux, the steps of filtering, washing and drying are also included.
[0057] As a preferred embodiment of the present invention, the condensation reflux is carried out under nitrogen protection.
[0058] As an embodiment of the present invention, the mass ratio of the waste plastics, triethylenetetramine and zinc acetate is 1:5 to 9:0.01.
[0059] As a preferred embodiment of the present invention, the waste plastics are waste PET plastics.
[0060] As a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned aging-resistant organic zirconium phosphate / polymer modified asphalt, comprising the following steps:
[0061] After preheating the base asphalt to 160-180°C, a polymer modifier and a solubilizer are added, and the mixture is sheared at a high speed (4000-5000rpm) at a temperature of 175-195°C for 50-70min; then, organic zirconium phosphate and sulfur are added, and the mixture is sheared at a high speed (4000-5000rpm) at a temperature of 175-195°C for 40-60min; then, the mixture is cooled to 165-185°C, and stirred at a low speed (1000-2000rpm) for 40-60min to obtain the aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0062] The aging-resistant organo-zirconium phosphate / polymer modified asphalt and the preparation method thereof of the present invention are further described below in conjunction with specific embodiments.
[0063] The room temperature involved in the specific implementation manner of the present invention specifically refers to 20-30°C.
[0064] The raw materials used in the specific implementation of the present invention are all common commercial products, among which the CAS number of ethyl isocyanate acrylate is 13641-96-8, the CAS number of isocyanoethyl methacrylate is 30674-80-7, the CAS number of vinyl trimethoxysilane is 2768-02-7, and the CAS number of 1,2,2,6,6-pentamethyl-4-(vinyl diethoxysilyloxy) piperidine (PMVP) is 14380-75-7. The matrix asphalt is specifically 70# matrix asphalt. Waste PET plastic flakes come from waste PET plastic bottles.
[0065] Example 1
[0066] An aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following raw materials, calculated by weight: 4 parts of organic zirconium phosphate, 7 parts of SBS, 100 parts of base asphalt, 2 parts of waste plastic degradation products, and 0.03 parts of sulfur.
[0067] The preparation method of aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following steps:
[0068] S1. Preparation of organic zirconium phosphate: weigh 3 parts of zirconium phosphate and add them to 300 parts of toluene, ultrasonicate for 20 minutes, and reflux at 100° C. for 30 minutes to obtain a zirconium phosphate-toluene mixture; add 2 parts of ethyl isocyanate acrylate to the zirconium phosphate-toluene mixture, and dropwise add 0.01 parts of dibutyltin dilaurate, reflux at 100° C. for 6 hours, then filter, wash with toluene, and vacuum dry to obtain an organic zirconium phosphate;
[0069] S2. Preparation of waste plastic degradation products: under nitrogen protection, waste PET plastic flakes, triethylenetetramine and zinc acetate in a mass ratio of 1:7:0.01 were added to a round-bottom flask, and the mixture was condensed and refluxed at 180° C. for 2 h, and then filtered, washed and dried to obtain waste plastic degradation products;
[0070] S3. Preparation of aging-resistant organic zirconium phosphate / polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS and waste plastic degradation products in proportion, and shear at a temperature of 180°C at a high speed (speed of 4500rpm) for 60min; then add organic zirconium phosphate and sulfur in proportion, and shear at a temperature of 180°C at a high speed (speed of 4500rpm) for 40min; then cool to 170°C, stir at a low speed (speed of 1500rpm) for 60min to obtain aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0071] Example 2
[0072] Same as Example 1, except that the number of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 2.
[0073] Example 3
[0074] Same as Example 1, except that the number of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 6.
[0075] Example 4
[0076] An aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following raw materials, calculated by weight: 4 parts of organic zirconium phosphate, 7 parts of SBS, 100 parts of base asphalt, 2 parts of waste plastic degradation products, and 0.03 parts of sulfur.
[0077] The preparation method of aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following steps:
[0078] S1. Preparation of organic zirconium phosphate: weigh 10 parts of zirconium phosphate and place them in a beaker, add 100 parts of deionized water, then add sodium hydroxide aqueous solution dropwise until the pH value of the solution reaches 10, stir at room temperature (speed is 1500 rpm) for 10 hours, then filter and wash until the filtrate is neutral, and dry to obtain hydroxylated zirconium phosphate; take 10 parts of hydroxylated zirconium phosphate and disperse them in 100 parts of deionized water, then add 100 parts of methanol solution of vinyltrimethoxysilane (40wt%) dropwise, stir (speed is 1500 rpm) for 3 hours, filter, wash and dry to obtain organic zirconium phosphate;
[0079] S2. Preparation of waste plastic degradation products: under nitrogen protection, waste PET plastic flakes, triethylenetetramine and zinc acetate in a mass ratio of 1:7:0.01 were added to a round-bottom flask, and the mixture was condensed and refluxed at 180° C. for 2 h, and then filtered, washed and dried to obtain waste plastic degradation products;
[0080] S3. Preparation of aging-resistant organic zirconium phosphate / polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS and waste plastic degradation products in proportion, and shear at a temperature of 180°C at a high speed (speed of 4500rpm) for 60min; then add organic zirconium phosphate and sulfur in proportion, and shear at a temperature of 180°C at a high speed (speed of 4500rpm) for 40min; then cool to 170°C, stir at a low speed (speed of 1500rpm) for 60min to obtain aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0081] Example 5
[0082] Same as Example 4, except that the number of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 2.
[0083] Example 6
[0084] Same as Example 4, except that the number of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 6.
[0085] Comparative Example 1
[0086] A polymer modified asphalt comprises, by weight, 7 parts of SBS, 100 parts of base asphalt, 2 parts of waste plastic degradation products, and 0.03 parts of sulfur.
[0087] The preparation method of polymer modified asphalt comprises the following steps:
[0088] S1. Preparation of waste plastic degradation products: under nitrogen protection, waste PET plastic flakes, triethylenetetramine and zinc acetate in a mass ratio of 1:7:0.01 were added to a round-bottom flask, and the mixture was condensed and refluxed at 180° C. for 2 h, and then filtered, washed and dried to obtain waste plastic degradation products;
[0089] S2. Preparation of polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS and waste plastic degradation products in proportion, and shear at a high speed (rotation speed is 4500rpm) at a temperature of 180°C for 60 minutes; then add sulfur in proportion, and shear at a high speed (rotation speed is 4500rpm) at a temperature of 180°C for 40 minutes; then cool to 170°C, stir at a low speed (rotation speed is 1500rpm) for 60 minutes to obtain polymer modified asphalt.
[0090] Comparative Example 2
[0091] An aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following raw materials in parts by mass: 4 parts of organic zirconium phosphate, 7 parts of SBS, 100 parts of base asphalt and 0.03 parts of sulfur.
[0092] The preparation method of aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following steps:
[0093] S1. Preparation of organic zirconium phosphate: weigh 3 parts of zirconium phosphate and add them to 300 parts of toluene, ultrasonicate for 20 minutes, and reflux at 100° C. for 30 minutes to obtain a zirconium phosphate-toluene mixture; add 2 parts of ethyl isocyanate acrylate to the zirconium phosphate-toluene mixture, and dropwise add 0.01 parts of dibutyltin dilaurate, reflux at 100° C. for 6 hours, then filter, wash with toluene, and vacuum dry to obtain an organic zirconium phosphate;
[0094] S2. Preparation of aging-resistant organic zirconium phosphate / polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS in proportion, and shear at high speed (4500 rpm) at 180°C for 60 minutes; then add organic zirconium phosphate and sulfur in proportion, and shear at high speed (4500 rpm) at 180°C for 40 minutes; then cool to 170°C, stir at low speed (1500 rpm) for 60 minutes to obtain aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0095] Comparative Example 3
[0096] Same as Example 1, except that the portion of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 1.
[0097] Comparative Example 4
[0098] Same as Example 1, except that the number of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 8.
[0099] Comparative Example 5
[0100] Same as Example 4, except that the portion of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer-modified asphalt component is 1.
[0101] Comparative Example 6
[0102] Same as Example 4, except that the number of organic zirconium phosphate in the aging-resistant organic zirconium phosphate / polymer modified asphalt component is 8.
[0103] Comparative Example 7
[0104] A zirconium phosphate / polymer modified asphalt, whose raw material compositions are, by weight, 4 parts of zirconium phosphate, 7 parts of SBS, 100 parts of base asphalt, 2 parts of waste plastic degradation products, and 0.03 parts of sulfur.
[0105] The preparation method of zirconium phosphate / polymer modified asphalt comprises the following steps:
[0106] S1. Preparation of waste plastic degradation products: under nitrogen protection, waste PET plastic flakes, triethylenetetramine and zinc acetate in a mass ratio of 1:7:0.01 were added to a round-bottom flask, and the mixture was condensed and refluxed at 180° C. for 2 h, and then filtered, washed and dried to obtain waste plastic degradation products;
[0107] S2. Preparation of zirconium phosphate / polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS and waste plastic degradation products in proportion, and shear at a temperature of 180°C at a high speed (rotation speed of 4500rpm) for 60min; then add zirconium phosphate and sulfur in proportion, and shear at a temperature of 180°C at a high speed (rotation speed of 4500rpm) for 40min; then cool to 170°C, stir at a low speed (rotation speed of 1500rpm) for 60min to obtain zirconium phosphate / polymer modified asphalt.
[0108] Comparative Example 8
[0109] An aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following raw materials, calculated by weight: 4 parts of organic zirconium phosphate, 7 parts of SBS, 100 parts of base asphalt, and 2 parts of waste plastic degradation products.
[0110] The preparation method of aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following steps:
[0111] S1. Preparation of organic zirconium phosphate: weigh 3 parts of zirconium phosphate and add them to 300 parts of toluene, ultrasonicate for 20 minutes, and reflux at 100° C. for 30 minutes to obtain a zirconium phosphate-toluene mixture; add 2 parts of ethyl isocyanate acrylate to the zirconium phosphate-toluene mixture, and dropwise add 0.01 parts of dibutyltin dilaurate, reflux at 100° C. for 6 hours, then filter, wash with toluene, and vacuum dry to obtain an organic zirconium phosphate;
[0112] S2. Preparation of waste plastic degradation products: under nitrogen protection, waste PET plastic flakes, triethylenetetramine and zinc acetate in a mass ratio of 1:7:0.01 were added to a round-bottom flask, and the mixture was condensed and refluxed at 180° C. for 2 h, and then filtered, washed and dried to obtain waste plastic degradation products;
[0113] S3. Preparation of aging-resistant organic zirconium phosphate / polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS and waste plastic degradation products in proportion, and shear at a high speed (speed of 4500rpm) at 180°C for 60min; then add organic zirconium phosphate in proportion, and shear at a high speed (speed of 4500rpm) at 180°C for 40min; then cool to 170°C, stir at a low speed (speed of 1500rpm) for 60min to obtain aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0114] Comparative Example 9
[0115] An aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following raw materials, calculated by weight: 4 parts of organic zirconium phosphate, 7 parts of SBS, 100 parts of base asphalt, 2 parts of waste plastic degradation products, and 0.03 parts of sulfur.
[0116] The preparation method of aging-resistant organic zirconium phosphate / polymer modified asphalt comprises the following steps:
[0117] S1. Preparation of organic zirconium phosphate: 10 parts of zirconium phosphate were dispersed in 100 parts of deionized water, and then 100 parts of a methanol solution of vinyltrimethoxysilane (40 wt%) were added dropwise, and the mixture was stirred (at a speed of 1500 rpm) for 3 h, filtered, washed, and dried to obtain an organic zirconium phosphate;
[0118] S2. Preparation of waste plastic degradation products: under nitrogen protection, waste PET plastic flakes, triethylenetetramine and zinc acetate in a mass ratio of 1:7:0.01 were added to a round-bottom flask, and the mixture was condensed and refluxed at 180° C. for 2 h, and then filtered, washed and dried to obtain waste plastic degradation products;
[0119] S3. Preparation of aging-resistant organic zirconium phosphate / polymer modified asphalt: After preheating the base asphalt to 170°C, add SBS and waste plastic degradation products in proportion, and shear at a temperature of 180°C at a high speed (speed of 4500rpm) for 60min; then add organic zirconium phosphate and sulfur in proportion, and shear at a temperature of 180°C at a high speed (speed of 4500rpm) for 40min; then cool to 170°C, stir at a low speed (speed of 1500rpm) for 60min to obtain aging-resistant organic zirconium phosphate / polymer modified asphalt.
[0120] Test Example 1
[0121] In order to verify the anti-aging performance of the modified asphalt, the modified asphalt in the above examples and comparative examples was subjected to asphalt segregation test according to the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) to analyze the asphalt storage stability. Then, the modified asphalt samples were subjected to short-term aging test (film oven test) according to the above specifications. On the basis of the short-term aging test, an ultraviolet aging test (ultraviolet light intensity 800w / m 2 , temperature is 60℃, aging time is 3 days), and a dynamic shear rheometer is used to perform temperature scanning experiments on the samples before and after aging, and the complex modulus aging index (CAI) is calculated to evaluate the anti-aging ability of asphalt. The smaller the value of the complex modulus aging index, the stronger the anti-aging ability of asphalt. The aging index calculation formula is as follows:
[0122]
[0123] Where: aging represents the index after aging, and origin represents the index before aging.
[0124] The performance test results are shown in Table 1:
[0125] Table 1
[0126]
[0127]
[0128] Among them, the softening point difference value is the softening point difference value between the upper and lower layers after the asphalt separation test. The larger the softening point difference value, the worse the asphalt storage stability, and the smaller the softening point difference value, the better the asphalt storage stability.
[0129] According to the experimental data recorded in Table 1, by comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the cross-linking of organic zirconium phosphate and polymer can significantly improve the storage stability of polymer-modified asphalt, and the addition of waste plastic degradation products further improves the storage stability of asphalt. In addition, the addition of organic zirconium phosphate greatly improves the ability of asphalt to resist ultraviolet aging.
[0130] By comparing Examples 1-3 with Examples 3 and 4 (and Examples 4-6 with Examples 5-6 as well), it can be seen that the combination of organic zirconium phosphate and polymer can improve the storage stability of asphalt and enhance the anti-ultraviolet aging ability of polymer-modified asphalt. During the preparation of modified asphalt, if the dosage of organic zirconium phosphate is too low, the improvement in asphalt performance is limited. As the dosage of organic zirconium phosphate increases, the improvement in asphalt performance gradually decreases. Considering the preparation cost, the dosage of organic zirconium phosphate should not be too high.
[0131] By comparing Example 1 and Comparative Example 7, it can be obtained that the organic treatment of zirconium phosphate is a necessary step to achieve the combination of zirconium phosphate and polymer, which is beneficial to the improvement of the storage stability and anti-aging performance of the modified asphalt.
[0132] By comparing Example 1 with Comparative Example 8, it can be seen that sulfur can increase the cross-linking density of the polymer and also has a certain promoting effect on improving the storage stability and anti-aging performance of the modified asphalt.
[0133] By comparing Example 4 with Comparative Example 9, it can be obtained that hydroxylation of zirconium phosphate is beneficial to improving the organic effect of zirconium phosphate, and is beneficial to the combination of zirconium phosphate and polymer, thereby improving the storage stability and anti-aging performance of asphalt.
[0134] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An aging-resistant organo-zirconium phosphate / polymer modified asphalt, characterized in that: Calculated by weight, the raw materials include: 2 to 6 parts of organic zirconium phosphate, 3 to 10 parts of polymer modifier, 100 parts of base asphalt, 1 to 3 parts of solubilizer, and 0.02 to 0.05 parts of sulfur.
2. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 1, characterized in that: The organic zirconium phosphate is obtained by surface-modifying zirconium phosphate with an organic surface modifier; the organic surface modifier is one of ethyl isocyanate acrylate, isocyanoethyl methacrylate, vinyl trimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyl diethoxysilyloxy) piperidine.
3. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 2, characterized in that: The organic surface modifier is one of ethyl isocyanate acrylate and isocyanoethyl methacrylate, and the preparation steps of the organic zirconium phosphate include: mixing zirconium phosphate and toluene to obtain a zirconium phosphate-toluene mixture; adding an organic surface modifier and a catalyst to the zirconium phosphate-toluene mixture, and refluxing at a temperature of 80 to 120° C. for 4 to 8 hours to obtain the organic zirconium phosphate; Alternatively, the organic surface modifier is one of vinyltrimethoxysilane and 1,2,2,6,6-pentamethyl-4-(vinyldiethoxysilyloxy)piperidine, and the preparation steps of the organic zirconium phosphate include: hydroxyl-modifying zirconium phosphate to obtain hydroxylated zirconium phosphate; dispersing the hydroxylated zirconium phosphate in water, then adding a methanol solution of the organic surface modifier, stirring the reaction for 2 to 4 hours, and obtaining the organic zirconium phosphate.
4. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 3, characterized in that: The mass ratio of the zirconium phosphate, toluene, organic surface modifier and catalyst is 3:270-330:1.5-2.5:0.01; Alternatively, the mass ratio of the hydroxylated zirconium phosphate, water and the methanol solution of the organic surface modifier is 1:8-12:8-12, and the concentration of the methanol solution of the organic surface modifier is 30-50wt%.
5. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 3, characterized in that: The step of mixing zirconium phosphate and toluene to obtain a zirconium phosphate-toluene mixture comprises: mixing zirconium phosphate and toluene, ultrasonically treating for 15 to 30 minutes, and then refluxing at a temperature of 80 to 120° C. for 20 to 40 minutes to obtain a zirconium phosphate-toluene mixture.
6. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 3, characterized in that: The hydroxyl-modification of zirconium phosphate to obtain hydroxylated zirconium phosphate includes: mixing zirconium phosphate and water, adjusting the pH of the mixed solution to 9 to 11, and stirring for 8 to 10 hours to obtain the hydroxylated zirconium phosphate.
7. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 1, characterized in that: The polymer modifier is a polymer containing double bonds in its structure.
8. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 1, characterized in that: The solubilizer is a degradation product of waste plastics; the preparation steps of the degradation product of waste plastics include: mixing waste plastics, triethylenetetramine and zinc acetate, condensing and refluxing at a temperature of 160 to 200° C. for 2 to 3 hours to obtain the degradation product of waste plastics.
9. The aging-resistant organo-zirconium phosphate / polymer modified asphalt according to claim 8, characterized in that: The mass ratio of the waste plastic, triethylenetetramine and zinc acetate is 1:5 to 9:0.
01.
10. The method for preparing the aging-resistant organo-zirconium phosphate / polymer modified asphalt according to any one of claims 1 to 9, characterized in that: The following steps are involved: After preheating the base asphalt to 160-180°C, a polymer modifier and a solubilizer are added, and high-speed shearing is performed at a temperature of 175-195°C for 50-70 minutes; then, organic zirconium phosphate and sulfur are added, and high-speed shearing is performed at a temperature of 175-195°C for 40-60 minutes; then, the temperature is lowered to 165-185°C, and low-speed stirring is performed for 40-60 minutes to obtain the aging-resistant organic zirconium phosphate / polymer modified asphalt.
Citation Information
Patent Citations
Organic zirconium phosphate modifier based on waste plastic derivative, anti-aging asphalt-based material and preparation method thereof
CN119101287A
Anti-aging polyurethane-zirconium phosphate composite modified asphalt and preparation method thereof
CN119101367A